IMPLIKASI ANTROPOLOGI DALAM SISTEM PENDIDIKAN DI INDONESIA - Rena Elia; Neviyarni; Irda Murni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study is to find out the implications for the education system in Indenseian by looking at the basic meanings and the relationship between Anthropology as a process of positive and negative meaning. The research method used is a qualitative description method by collecting library data, reading and recording and processing research materials. Research result . In multicultural education, educational anthropology has an impact on positive educational outcomes for students, it is clear that multicultural education and educational anthropology are both committed to conducting research and improving learning outcomes. Contextually, cultural anthropologists highlight various studies on the diversity differences that exist in the characteristics of human behavior patterns in communities.